Analysis of the Effect of Brand Image, Perceived Quality and Price on Purchasing Decisions for Irawan Shrimp Feed at CV. Windu Lestari - Muhammad Ali Akbar (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
This study aims to determine the effect of Brand Equity on pesticide sales at PT. Panca Kurnia Niaga Nusantara, knowing the effect of the Distribution Channel on the sale of pesticides at PT. Panca Kurnia Niaga Nusantara, and know the effect of Brand Equity and Distribution Channels on the sale of pesticides at PT. Panca Kurnia Niaga Nusantara. The population in this study are customers of PT. Panca Kurnia Niaga Nusantara as many as 87 stores. The sampling technique in this study used saturated samples and obtained as many as 87 stores. The research method used is the technique of collecting data through questionnaires. The results showed that Brand Equity and Distribution Channel simultaneously have a positive and significant effect on the sale of pesticides at PT. Panca Kurnia Niaga Nusantara . While the remaining is effected by other factors originating from outside this research model such as price, service quality, customer satisfaction.